Preparation, optical characterization and stability of gold nanoparticles by facile methods - González, V; Kharisov, Boris I.; Gómez de la Fuente, María Idalia del Consuelo (Sociedad Mexicana de Física A.C., 2019)
Gold nanoparticles were obtained by reduction of chloroauric acid HAuCl4 by two methods: conventional heating and microwave synthesis. In the microwave method, different cycles and sonication time were analyzed to establish the synthesis with smaller nanoparticle size and higher absorbance. The influence of synthesis method, cycles quantity and sonication time in the gold nanoparticles size and plasmon resonance were studied. Gold nanoparticles were analyzed by UV-Vis spectrophotometry, dynamic light scattering and surface electron microscopy. The results indicate that the nanoparticles obtained by microwave have bigger size than those obtained by conventional heating, however, present higher absorption. The microwave nanoparticles were analyzed one year after its synthesis and it was found that the plasmon resonance signal remains almost unchanged. Finally, two equations were derived from the analyzes for estimate molar extinction coefficient, molar concentration, and nanoparticle average diameter.